Epithelial cell proliferation in the sigmoid colon of patients with adenomatous polyps increases during oral calcium supplementation. - Kleibeuker, J. H. (Nature Publishing Group, 1993)
To study the effect of oral supplemental calcium on colonic epithelial proliferation, 17 adenomatous polyp patients received 1.5 g Ca2+ as calcium carbonate daily during 12 weeks, while on a calcium constant diet, based on the patients' habitual diet. Seven subsequently continued calcium supplementation for 9 months without dietary restrictions. Epithelial proliferation rate in colonic biopsies, expressed as labelling index (%), was determined with 5-bromodeoxyuridine and immunohistochemistry. Biopsies were taken from the midsigmoid at time of polyp excision and at the end of the intervention period. Median labelling index increased from 6.1% before to 8.7% after 12 weeks calcium (n = 17, P < 0.02). This was due to increased labelling in the basal third of the crypts (11.9 vs 16%), whereas labelling in mid and luminal compartments was not affected. Labelling index remained increased after 1 year calcium supplementation at 8.8%. Crypt length was not affected by calcium. These results are in contrast to those of others, who have shown a decrease of rectal epithelial proliferation during similar doses of calcium. Therefore, the effect of nutritional intervention on colonic epithelial proliferation should be studied in biopsies taken not only from the rectum, but also from more proximal parts of the colon. Caution with respect to large scale intervention studies with calcium in high risk groups is mandatory.